ANALISIS DISIPLIN KERJA KARYAWAN PADA PT GS SALON MOBIL DI KOTA TANGERANG - Dimas Khalifah Jendar Bumi; Hira Maulida (Journal of Research and Publication Innovation, 2025)
This research aims to analyze employee work discipline. The research was conducted at PT GS Salon Mobil Tangerang City. The method used in this research uses a qualitative method through a descriptive approach. The instruments used are interviews, documentation and SWOT analysis. The information obtained in this research came from 2 (two) informants, namely the company owner (owner) and financial manager and 5 (five) research sources, namely employees of PT GS Salon Mobil Tangerang City. Data analysis techniques use data collection, data reduction, data presentation, data verification and checking data validity. The results of the research conducted show that the form of implementation of employee work discipline at PT GS Salon Mobil in Tangerang City can be seen from the ability of employees to complete work well, follow directions or orders from leaders and of course employee obedience to all regulations in force at the company PT GS Salon Mobil Kotak Tangerang. Obstacles to employee work discipline at PT GS Salon Mobil in Tangerang City are factors of fairness and firmness of the leadership or management in providing solutions to problems or incidents that occur in the work environment. The suggestion that can be given from the results of this study is the need for a standardized assessment through Key Performance Indicators (KPI) that can be carried out by leaders in conducting assessments and as evaluation material for employees. The importance of an attitude of fairness and firmness in overcoming obstacles to employee work discipline and strategies that can be implemented to improve work discipline, namely by providing other compensation in the form of incentives, health benefits and performance bonuses.